Relationship between Knowledge Management and Managerial Skills: The Role of Creative Thinking - Ali Shamsi (Foresight and STI Governance)
Knowledge management is one of the most critical issues  the managers of organizations, especially educational organizations, must consider. It is aimed at finding new viewpoints about learning, creating knowledge, and developing internal and external competences. This paper investigates the relationship between management skills and knowledge management mediated by creative thinking. The analysis is based on a survey of several hundred managers and teachers at high schools in Isfahan. The research employs a step-by-step regression analysis and structural equations modeling.